EFEK PROBIOTIK PADA APLIKASI KADAR PROTEIN KASAR (PK) PAKAN YANG BERBEDA TERHADAP EFISIENSI PAKAN AYAM KAMPUNG - Eka Fitasari; Akhadiyah Afrila (Universitas Tribhuwana Tunggadewi, 2015)
The using of probiotic become crucial as a natural feed additive to increase the production of native chicken and avoid the using of antibiotic which can leave bad residue in poultry meat. This research used 2 kinds of bacteria were probiotic A (Bacillus spp) and probiotic B (mixing bacteria) on four feed treatments were BR 1 (factory feed production that contain 21-23% protein), feed formulation corn-soybean basic contain 20%, 19% and 18% crude protein. The research used Nested method, there were 8 treatments and replication 3 times. The result showed that treatments combination didn’t give significant effect (p>0.05) on feed consumption, final weight, FCR (feed consumption ratio), and carcass weight, but it gave very significant effect on meat fat (p